2020
DOI: 10.1101/2020.08.25.265561
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 infection of human iPSC-derived cardiac cells predicts novel cytopathic features in hearts of COVID-19 patients

Abstract: COVID-19 causes cardiac dysfunction in up to 50% of patients, but the pathogenesis remains unclear. Infection of human iPSC-derived cardiomyocytes with SARS-CoV-2 revealed robust transcriptomic and morphological signatures of damage in cardiomyocytes. These morphological signatures include a distinct pattern of sarcomere fragmentation, with specific cleavage of thick filaments, and numerous iPSC-cardiomyocytes that lacked nuclear DNA. Human autopsy specimens from COVID-19 patients also displayed marked sarcome… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
84
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(97 citation statements)
references
References 62 publications
13
84
0
Order By: Relevance
“…Other studies demonstrated that SARS-CoV2 can enter and replicate within human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes and induce cytotoxic effects that abolish cardiomyocyte beating [ 78 , 79 , 80 ]. SARS-CoV-2 enters cells by binding of the viral Spike protein (S) to the SARS-CoV2 receptor ACE2 and S priming by the serine protease TMPRSS2 [ 81 ].…”
Section: Macrophage Role In Cardiac Inflammation and Cardiac Dysfumentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies demonstrated that SARS-CoV2 can enter and replicate within human-induced pluripotent stem cell (hiPSC)-derived cardiomyocytes and induce cytotoxic effects that abolish cardiomyocyte beating [ 78 , 79 , 80 ]. SARS-CoV-2 enters cells by binding of the viral Spike protein (S) to the SARS-CoV2 receptor ACE2 and S priming by the serine protease TMPRSS2 [ 81 ].…”
Section: Macrophage Role In Cardiac Inflammation and Cardiac Dysfumentioning
confidence: 99%
“…SARS-CoV-2 enters cells by binding of the viral Spike protein (S) to the SARS-CoV2 receptor ACE2 and S priming by the serine protease TMPRSS2 [ 81 ]. Studies by Perez-Bermejo et al [ 80 ] examined the expression of ACE2 and TMPRSS2 in hiPSC-derived cardiomyocytes. ACE2 was expressed by the hiPSC-derived cardiomyocytes but not TMPRSS2.…”
Section: Macrophage Role In Cardiac Inflammation and Cardiac Dysfumentioning
confidence: 99%
“…To investigate the possibility of viral integration into virus infected cells we analyzed published RNA-Seq data from SARS-CoV-2 -infected cells for evidence of chimeric transcripts, which would be indicative of viral integration into the genome and expression. Examination of these data sets [24][25][26][27][28][29][30] (Fig. S1a-b) revealed a substantial number of host-viral chimeric reads (Fig. 1a-c, S1c).…”
Section: Expression Of Viral-cellular Chimeric Transcripts In Infectementioning
confidence: 99%
“…These extrapulmonary manifestations include myocarditis, acute kidney injury, hepatocellular injury, gastrointestinal disease and increasing evidence for both PNS and CNS pathology 118,119 . There has been a rapid response from the stem cell field in engineering both 2D models and 3D organoids to study the tropism of SARS-CoV-2 in human gut enterocytes 120 and intestinal organoids 121,122 , cardiomyocytes [123][124][125] , kidney organoids 126 , liver organoids 124 , pancreatic endocrine cells 124 and, of course, lung organoids 127 .…”
Section: Models For Sars-cov-2 Infectionmentioning
confidence: 99%